EDUKASI DAN PELAYANAN FISIOTERAPI UNTUK MENGURANGI DISMENORE PADA REMAJA DI SMPN 2 PEMATANGSIANTAR - Isa Harpika Br. Ginting; Yeni Trisna Purba; Imelda Putri Arianti (Yayasan Nusantara Hasana Berdikari, 2024)
This community service study focuses on dysmenorrhea, a common health issue among adolescents that can negatively affect academic and social performance. Dysmenorrhea has a high prevalence among adolescents (up to 94%), highlighting the need for effective management strategies. The program was implemented at SMP Negeri 2 Pematangsiantar to educate students and provide physiotherapy interventions to alleviate menstrual pain. The intervention included education about the causes, mechanisms, and management of dysmenorrhea, as well as practical physical exercises (dysmenorrhea exercises). A quasi-experimental design with pre-test and post-test measures was used to evaluate the outcomes. The results demonstrated a significant increase in participants’ knowledge after the intervention. The program aims not only to improve understanding but also to support reduced pain intensity, better quality of life, and improved academic performance among participating students.